Estimating Abundance of an Unmarked, Low‐Density Species using Cameras. Issue 1 (3rd September 2020) - Loonam, Kenneth E.; Ausband, David E.; Lukacs, Paul M.; Mitchell, Michael S.; Robinson, Hugh S.
ABSTRACT: Estimating abundance of wildlife populations can be challenging and costly, especially for species that are difficult to detect and that live at low densities, such as cougars ( Puma concolor ). Remote, motion‐sensitive cameras are a relatively efficient monitoring tool, but most abundance estimation techniques using remote cameras rely on some or all of the population being uniquely identifiable. Recently developed methods estimate abundance from encounter rates with remote cameras and do not require identifiable individuals. We used 2 methods, the time‐to‐event and space‐to‐event models, to estimate the density of 2 cougar populations in Idaho, USA, over 3 winters from 2016–2019. We concurrently estimated cougar density using the random encounter model (REM), an existing camera‐based method for unmarked populations, and genetic spatial capture recapture (SCR), an established method for monitoring cougar populations. In surveys for which we successfully estimated density using the SCR model, the time‐to‐event estimates were more precise and showed comparable variation between survey years. The space‐to‐event estimates were less precise than the SCR estimates and were more variable between survey years. Compared to REM, time‐to‐event was more precise and consistent, and space‐to‐event was less precise and consistent. Low sample sizes made the space‐to‐event and SCR models inconsistent from survey to survey, and non‐random camera placement may have biased both of the camera‐based estimators high. We show that camera‐based estimators can perform comparably to existing methods for estimating abundance in unmarked species that live at low densities. With the time‐ and space‐to‐event models, managers could use remote cameras to monitor populations of multiple species at broader spatial and temporal scales than existing methods allow. © 2020 The Wildlife Society. Abstract : Recently developed methods for estimating abundance from remote cameras without marked individuals performed comparably to existing, intensive methods on 2 populations of cougars in Idaho, USA, 2017–2019. With camera‐based methods for estimating abundance without marked individuals that work for species that live at low densities, large‐scale, multi‐species monitoring could be more feasible.